Asymmetric electoral authoritarianism? The case of the 2021 elections in Ethiopia. Issue 172 (3rd April 2022) - Lyons, Terrence; Verjee, Aly
SUMMARY: Ethiopia's 2021 elections have been overshadowed by the brutal civil war that has raged since November 2020. The elections may not have been competitive but they reveal important dynamics about institutions and the competition for power in Africa's second most populous state. These were the first elections under Prime Minister Abiy Ahmed, who came to power in 2018 insisting that legitimacy comes through elections. By 2021, however, repression and boycotts resulted in the ruling party winning 97% of the seats where voting took place. Beneath this national result were patterns of asymmetric electoral authoritarianism. Some regions experienced heavy-handed political domination and voting with only the ruling party competing. Others had circumscribed political space and opportunities for the opposition to win votes. Local dynamics challenge assessments that only look at the national outcome, missing important differences between types of electoral authoritarianism.